SA-9 Mucinous Mamari Carsinoma and Mammary Adenoma in Young Cat - Ester Sembiring (Hemera Zoa, 2018)
Cat mammary tumors commonly occur in female cats above 9 years of age. The 85% mamae tumor in cats is malignant, characterized by rapid growth and spread. The cat race that has the highest presdiposis factor is Persian, followed by Siamse, and Mancoon. Mamae's tumor in Mimika cat occurs at the age of 6 months, Mimika is a female cat with a Maincoon race.